GC Insights: Lessons from participatory water quality research in the upper Santa River basin, Peru - Rangecroft, Sally (2024)
Here we share four key lessons from an interdisciplinary project (Nuestro Rio) that gathered community perspectives on local water quality in the Santa River basin (Peru) utilising a digital technological approach where we collected data via a novel photo elicitation app, supported by a field work campaign. The lessons explored in this article provide insights into challenges and opportunities for researchers considering developing technological tools for encouraging participation and engagement in marginalised communities.